2022
DOI: 10.1002/adfm.202205002
|View full text |Cite
|
Sign up to set email alerts
|

A DNA Aptamer Targeting Cellular Fibronectin Rather Than Plasma Fibronectin for Bioimaging and Targeted Chemotherapy of Tumors

Abstract: Fibronectin (FN) is a well-established hallmark of epithelial-to-mesenchymal transition, and may serve as an omnipresent cancer biomarker regardless of the origins of tumor cells. An ssDNA aptamer (ZY-1) with highly selective binding affinity to mesenchymal stromal cells is previously developed, but the binding target of ZY-1 on the cells and the underlying mechanism is yet to be understood. Here, the identification of FN as the target protein of aptamer ZY-1 is reported for the first time and the mechanism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Finally, ELISA was used to determine the changes in fibronectin (FN) and SNAIL proteins after regulation to clarify the other EMT-related protein changes in mice tumors after miR-200a-3p overexpression. FN and SNAlL are recognized as EMT-related proteins, depicting the enhanced invasion and metastasis ability of tumor cells [ 22 , 23 ]. The experimental results indicated that the expression of FN and SNAIL in tumors in the miR-200a-3p-overexpressing group was decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, ELISA was used to determine the changes in fibronectin (FN) and SNAIL proteins after regulation to clarify the other EMT-related protein changes in mice tumors after miR-200a-3p overexpression. FN and SNAlL are recognized as EMT-related proteins, depicting the enhanced invasion and metastasis ability of tumor cells [ 22 , 23 ]. The experimental results indicated that the expression of FN and SNAIL in tumors in the miR-200a-3p-overexpressing group was decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the integration of siRNA with poly­(dimethylaminoethyl methacrylate) cationic polymer brushes coating, leveraging their unique physicochemical properties, has yielded high-performance theranostic probes . Additionally, aptamers have gained recognition as versatile agents in precision medicine, facilitating targeted drug therapy, , personalized treatments, molecular diagnostics, tumor marker discovery, bioanalysis, molecular pathology, , noninvasive screening, and bioimaging. , These recent advances in aptamer research hold tremendous potential for accelerating progress in precision medicine and modern biological applications. Besides, a novel regulatory network involving long noncoding RNAs (lncRNAs), miRNAs, and mRNAs, commonly known as the lncRNA-miRNA-mRNA axis, has been implicated in the pathophysiological processes of colorectal cancer and cardiovascular diseases .…”
Section: Chemical Modification-assisted Better Rna Therapeuticsmentioning
confidence: 99%
“…Aptamer is a class of synthetic oligonucleotide ligands with antibody-like binding behavior with designated molecular targets 39 41 , which has attracted broad interest for therapeutic applications due to the high binding affinity/specificity and may fulfill a variety of functional roles including signaling mediators and targeting ligands, which are particularly favorable in the field of antitumor immunotherapeutics 42 46 . For example, CpG ODN (CpG oligonucleotide) is a clinically tested aptamer-based immune adjuvant that can promote DC activation via triggering toll-like receptor 9 (TLR9) immune signaling to stimulate the downstream adaptive immune reactions 47 49 .…”
Section: Introductionmentioning
confidence: 99%